Development and validation of a table tennis serve skill assessment instrument for junior high school students: A psychometric approach - Alfani, Muhammad Aliffajaruddin; Winarno, M. E.; Nurrochmah, Siti (Physical Education and Sports: Studies and Research, 2025)
Background: The highest assessment weight in physical education lessons lies in psychomotor skills. In order to find out how far the competencies possessed by students, a clear and comprehensive assessment tool or instrument is needed. Objectives: The research aims to develop a test instrument for forehand and backhand service skills in table tennis small ball games. Methods: The development of this instrument uses a research and development scheme, with predetermined steps (1) determining objectives, (2) analyzing literature, (3) developing specifications, (4) administering, (5) conducting tests, (6) analyzing data validity, reliability, and objectivity. The cluster sampling procedure was conducted on students aged 13-15 who met the inclusion criteria, involving junior high school students (n=80), consisting of 41 female students and 39 male students. Data were analyzed using IBM SPSS Statistics version 11.0. The basis for decision-making is the Pearson correlation test. The analysis technique in the reliability test uses a test and retest external estimation approach. Results: The forehand serve variable has a calculated r-value of 0.456> r-table 0.312, and the backhand serve variable obtained a calculated R-value of 0.352> r-table 0.312, so the table tennis skill instrument on that variable was declared valid. At the same time, the reliability test shows a value above 0.70; the instrument that has been prepared can be declared reliable. Conclusions: The assessment instrument for forehand and backhand serve skills in table tennis games for junior high school students has met the validity and reliability criteria. This shows that the instrument is suitable for teachers as an objective and consistent measuring tool in evaluating basic table tennis skills in students. Recommendations for future studies are encouraged to expand the sample size and integrate digital features to enhance the scalability and objectivity of the assessment.